Flouting Maxim By Sherlock Holmes and dr. Watson In Tv Series Of Sherlock Season - Affifatusholihah, Lina; Setyawan, Agustinus Hary (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractIn running daily activities, people will always meet and interact with other people, and language is a medium that is used by humans to interact with each other. In a conversation or discussion, everyone should pay attention to the four maxims in order that there are no errors in communication. However, it is not uncommon that the four rules above are breached by the speakers. This is called non-observance of the maxims, and one of a non-observance of the maxims that often occurs in is flouting maxim. The aims of this paper are to describe types of maxims that are flouted by Sherlock Holmes and dr. Watson as well as to describe how the maxims are flouted in Sherlock TV series season 1. This research used qualitative descriptive method. The researcher classifies the utterances to know what kind of maxim which are flouted, categorizes those into the category based on the Grice’s theory of Cooperative Principle, namely: maxim of quantity, quality, relation and manner. The research procedure begin by searching the script in the internet, matching the utterances in the script and in film and sorting the utterances between Sherlock Holmes and dr. Watson as well observing every word or sentence which are flouted by the main characters. The findings find that all kinds of maxims are flouted by Sherlock and dr. Watson. The result of analysis shows that the maxim flouted when the speakers say something irrelevant; something roguishness or lied to hide the truth in the form of rhetorical question; the information becomes more or too informative than what is required; and something obscurity of expression, ambiguity, or unnecessary prolixity.